Greater working memory in cochlear implant users is related to higher subjective quality of life - Prince, Priyanka; Chen, Joseph; Le, Trung; Lin, Vincent; Dimitrijevic, Andrew (Frontiers in Audiology and Otology, 2024)
Introduction A common concern for individuals with moderate-to-profound hearing loss who have received a cochlear implants (CIs) is difficulty following conversations in noisy environments. A possible reason is the increased use of cognitive resources (attention and working memory) to disambiguate the speech stimuli potentially causing detriments in functional aspects of life. However, this relationship is not well-documented. The overall arching goal of this study was to quantify the relationships between Patient-Reported Outcome Measures (PROMs) and cognitive ability through working memory and speech perception measures. Methods In the current study, 31 adult CI users and typical hearing (TH) age-matched controls were recruited. CI users completed PROMs including Speech, Spatial and Quality of hearing survey (SSQ) and versions of a quality of life (QOL) for CI users (CIQOL) and Nijmegen Cochlear Implant Questionnaire (NCIQ). Measures of cognition were assessed using internet-based tools. Outcomes were compared between groups and PROMs and were related to the cognitive tasks. Results Reduced auditory working memory and speech perception in noise were observed in CI users compared to TH controls. Correlation analyses revealed significant domain-specific PROM relationships with cognitive tasks in CI users, but not in TH controls. The SSQ had more significant relationships compared to the other PROMS. Conclusion These results suggest that internet-based metrics of cognitive ability are associated with the functional hearing aspects of life in CI users and that SSQ is more sensitive to investigate the cognitive related effects of QOL compared to other commonly used PROMs.